2015
DOI: 10.1007/s00198-015-3416-3
|View full text |Cite
|
Sign up to set email alerts
|

Optimal serum cholesterol concentrations are associated with accelerated bone loss in African ancestry men

Abstract: Purpose Studies of lipid and lipoprotein cholesterol associations with bone mineral density (BMD) and bone loss have been inconclusive, and longitudinal data are sparse. Therefore, the aim of this study was to test if fasting serum lipid and lipoprotein cholesterol levels are associated with areal and volumetric BMD and BMD change, Methods We determined the association of serum triglycerides, high-density lipoprotein (HDL) and low-density lipoprotein (LDL) cholesterol concentrations with cross-sectional and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 44 publications
(35 reference statements)
3
11
1
Order By: Relevance
“…Many studies have investigated the association between serum TG or HDL-C level and BMD. However, the conclusions between studies are controversial ( 8 , 9 , 17 27 , 36 40 ). In a Dutch cross-sectional, population-based study (including 620 men, 635 women aged 65–88 years), men and women in the highest quartile of HDL-C level had a significantly lower BMD compared with men and women in the lowest quartile ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have investigated the association between serum TG or HDL-C level and BMD. However, the conclusions between studies are controversial ( 8 , 9 , 17 27 , 36 40 ). In a Dutch cross-sectional, population-based study (including 620 men, 635 women aged 65–88 years), men and women in the highest quartile of HDL-C level had a significantly lower BMD compared with men and women in the lowest quartile ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…A large Swedish study of 6,886 women performed by Lidfeldt et al found a positive correlation between TG level and BMD and a negative correlation between TC or HDL level and BMD ( 38 ). Another cohort of 1,289 African ancestry men with a lower serum TG or LDL and higher HDL level exhibited an association with lower trabecular BMD ( 27 ). Furthermore, a retrospective analysis of data from 4,613 premenopausal women and 2,661 postmenopausal women aged 20–91 years showed no significant relationship between lipid profiles (TC, TG) and total hip, femoral neck, trochanter, or lumbar spine BMD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the association between serum lipid and bone metabolism has gained considerable interest; however, there is no general agreement regarding this subject yet. Retrospective studies conducted in postmenopausal women have reported a negative correlation between serum total cholesterol (TC), LDL-C levels, and bone mineral density (BMD) ( 10 12 ), while high-density lipoprotein-cholesterol (HDL-C) level was inversely associated with BMD in both men and women ( 11 , 13 16 ). In addition, cholesterol-reducing medication, such as statins, was reported to have beneficial effects on BMD in most previous studies ( 17 19 ); this also suggests the negative association between serum cholesterol levels and BMD.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies suggest that dyslipidemia could result in both increased bone resorption and decreased bone formation [1]. Various studies have tried to evaluate the association between lipid level and osteoporosis, but the results were proved to be controversial [1][2][3][4][5][6][7]. Some studies found an inverse relationship with bone mineral density (BMD) [1][2][3][4][5], whereas others have shown a positive correlation [6] or no correlation [7].…”
Section: Introductionmentioning
confidence: 99%